Effectiveness of open-source Android artificial pancreas systems for glucose management in patients with type 1 diabetes: a real-world study - Qin Wang; Xianming Li; Wenhao Zhang; Hao Wang; Jie Tang; Yu Ding; Xueying Zheng; Sihui Luo (Therapeutic Advances in Endocrinology and Metabolism, 2025)
Background: Practice of Open-source Android artificial pancreas systems (AAPS) among Chinese patients is increasing, but data on their effectiveness is lacking. Objectives: This study evaluates the effectiveness of AAPS compared with sensor-augmented pump (SAP) therapy among people with type 1 diabetes (T1D) in China. Design: A real-world, case-control study. Methods: We conducted this study among patients with T1D who had used AAPS or SAP therapy for >3 months. Propensity score matching (1:1) based on onset age, duration, gender, and baseline tight glucose range (time in the tight glucose range (TITR) 70–140 mg/dL) was performed. Key glycemic outcomes were analyzed. Results: One hundred forty-two T1D people using AAPS and 142 matched people receiving SAP therapy were included (56.00% female). Age and duration of T1D were 26.40 (interquartile range (IQR) 11.30–34.70) and 3.20 (IQR 0.87–9.12) years, respectively. Baseline TITR and time in the target glucose range (TIR) of 70–180 mg/dL were 57.10 ± 18.30% and 79.30% (IQR 68.50–88.30), respectively. After 3 months, the AAPS group had better TITR (60.52 ± 14.57% vs 56.20 ± 17.22%, adjusted difference, 3.91%; p  < 0.05) and TIR (79.12 ± 11.24% vs 77.37% (IQR 64.51–85.87), adjusted difference, 3.42%; p  < 0.001) compared with the control group. In addition, time in hypoglycemia was shorter in the AAPS group than in the control group during the study (4.05% (IQR 2.52–6.78) vs 5.68% (IQR 2.69–10.11); adjusted difference, −1.17%; p  < 0.05). Stratified analysis showed females, with a baseline glucose management indicator (GMI) < 7% and those aged over 18 years benefit more in the AAPS group. After adjusting for age, gender, duration of T1D, and baseline GMI, logistic regression analysis showed the AAPS group had a higher percentage of TITR improvement >5% than that in the control group (odds ratio = 1.73, 95% confidence interval (1.03, 2.92), p  < 0.05). Conclusion: AAPS is associated with significant improvements in glycemic control, without increasing hypoglycemia, compared to SAP therapy.